Hubungan Antara Pengetahuan, Sikap Dan Perilaku Dengan Kejadian Anemia Remaja Putri Kelas X Dan Xi Sma Negeri 1 Polokarto - Caturiyantiningtiyas, Titin, Bejo Raharjo, SKM, M.Kes, Dwi Astuti, SKM., M.Kes (2015)
Anemia is a condition in which the levels of hemoglobin and erythrocytes is lower than normal. The purpose of this study was to determine the relationship between knowledge, attitudes and behavior on the incidence of anemia among adolescent girls in the class X and XI 1 Polokarto high school. This research uses the analytic survey with cross sectional approach. The population of teenage girl of SMA Negeri 1 Polokarto. Data was collected by distributing questionnaires and levels of hemoglobin value obtained from venous blood sampling with digital tools brands touch easy. The population in this study was student of class X and XI as many as 356 students. The samples in this study were 180 students, sampling using Simple Random Sampling technique while using a statistical test Chi Square test). The results showed that there is a correlation between the level of knowledge with teenage girl in SMAN 1 Polokarto Sukoharjo (p = 0.03; RP: 1.22 ;95% CI: 0.67 to 0.99). There is a relationship between the attitude of teenage girls with anemia in SMAN 1 Polokarto Sukoharjo (p = 0.03; RP: 1.22 ;95% CI: 1.00 to 1.50). There is a relationship between the behavior of the incident teenage girls anemia in SMAN 1 Polokarto Sukoharjo (p = 0.02; RP: 0.80 ;95% CI: 0.66 to 0.98)